STRATEGY FOR IMPLEMENTING THE REGULATION OF ILLEGAL BUILDINGS TO IMPROVE THE QUALITY OF OPEN SPACES IN THE PANAKKUKANG DISTRICT AREA, MAKASSAR CITY - Tamsil, Erni; Muin, Sri Andrianti; Insan, A. Nur (Universitas Ichsan Sidenreng Rappang, 2025)
This study aims to analyze and formulate the implementation strategy for controlling illegal buildings in order to improve the quality of open spaces in the Panakkukang District area of Kota Makassar. The main problem addressed is the proliferation of illegal buildings that utilize public open spaces in ways that are inconsistent with their designated functions, resulting in environmental degradation, reduced social function of open spaces, and disruption of orderliness and urban aesthetics. This research employs a qualitative approach using a descriptive-analytical method. Data were collected through field observations, in-depth interviews with government officials, community leaders, and affected residents, as well as documentation studies. The analysis was conducted by identifying supporting and inhibiting factors in the implementation of building control policies, including regulatory aspects, inter-agency coordination, community participation, and resource availability. The results indicate that the implementation of illegal building control has not been optimal due to weak supervision, limited resources, lack of policy socialization, and resistance from affected communities. The recommended strategies include strengthening regulations and consistent law enforcement, enhancing cross-sectoral coordination, adopting persuasive and participatory approaches toward the community, providing feasible relocation alternatives, and optimizing the function of open spaces through community needs-based planning.